2018
DOI: 10.1002/pc.25197
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermo‐mechanical characterization of glass ionomer‐filled dental composite

Abstract: In this study, the effect of adding glass ionomer (GI) Restorative Cement (0−30 wt%) on the mechanical and thermo‐mechanical characterization of dental composite has been discussed. The characterization of dental composites was done by performing Fourier transform infrared spectroscopy, hardness test, compression test, flexural strength test, dynamic mechanical analysis (DMA), thermo gravimetric analysis (TGA). The finding of experiments indicated that the addition of 10 wt% of GI increased the water hardness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Glass ionomer, when combined with conditioner, is most successful when used in atraumatic restorative treatment (ART) [30] . Bonding 10% glass ionomer filler to resin-based composites increases physical properties such as hardness, flexural strength and compressive strength [31] . The shrinkage effect of Ketac Molar Aplicap and Ketac Molar Quick Aplicap glass ionomers is less than that of polymerized RMGIC when the material is light cured [26] .…”
Section: Glass Ionomermentioning
confidence: 99%
“…Glass ionomer, when combined with conditioner, is most successful when used in atraumatic restorative treatment (ART) [30] . Bonding 10% glass ionomer filler to resin-based composites increases physical properties such as hardness, flexural strength and compressive strength [31] . The shrinkage effect of Ketac Molar Aplicap and Ketac Molar Quick Aplicap glass ionomers is less than that of polymerized RMGIC when the material is light cured [26] .…”
Section: Glass Ionomermentioning
confidence: 99%
“…Better performance of composite can be achieved by using the concept of nanotechnology. Addition of nanofiller enhanced the mechanical properties of polymer composite 12–14 . The mechanical properties and thermal resistance of WPC was improved by adding nanosilica filler 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of nanofiller enhanced the mechanical properties of polymer composite. [12][13][14] The mechanical properties and thermal resistance of WPC was improved by adding nanosilica filler. 15,16 Biodegradable and biocompatible polymers exhibit "shape recovery property" which allows them to quickly recover their original shape under the environment temperature more than glass transition temperature.…”
mentioning
confidence: 99%
“…Therefore, resin modified glass ionomer was developed and showed better mechanical properties. [11,12] In another research, it was suggested to use dental composites with calcium type pre-reacted glass-ionomer (PRG-Ca) fillers as a good alternative for restoration. It was reported that adding 40 wt% of calcium type prereacted glass-ionomer enhanced re-mineralizing potential, increased degree of conversion, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, resin modified glass ionomer was developed and showed better mechanical properties. [ 11,12 ]…”
Section: Introductionmentioning
confidence: 99%